Analysis of English Learning Needs in Elementary Schools within the Independent Curriculum: A Learning Study in Grade III - Intan Cahyani Trinita; Gede Wira Bayu; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2024)
The low suitability of students' learning needs in learning English means that the learning process is monotonous, the class situation is passive and unreliable. Lack of teacher readiness in implementing English language learning in the Independent Curriculum. This research aims to analyze the needs for implementing English language learning and teacher readiness in learning English in the Merdeka curriculum. The research method used is descriptive qualitative. The data collection techniques used were observation, interviews and questionnaires. The research results show that the analysis of English language learning needs in class III elementary school in the Merdeka curriculum shows that the majority of students have difficulty understanding English material presented with a conventional approach. Students are more interested in interactive learning methods, such as the use of learning media. In addition, teachers expressed that they needed further training regarding the use of more flexible and creative approaches and more interesting learning aids. Based on the research results, it can be concluded that learning English in class III elementary school in the independent curriculum requires a more interactive, flexible and technology-based approach. This research has implications for the analysis of English language learning in elementary schools in the Merdeka curriculum, with a more communicative learning approach with technology support and teacher training to optimize learning.